The Effect of Soil Compaction Methods on Building Stability in Earthquake Prone Areas - Ramdan Yusuf; Haziq Idris; La One (Journal of Moeslim Research Technik, 2024)
Soil compaction plays a crucial role in determining the stability of structures, particularly in earthquake-prone regions. Inadequate compaction can lead to soil liquefaction and settlement, increasing the risk of structural failure during seismic events. Understanding the impact of different soil compaction methods is essential for enhancing building resilience. This study aims to evaluate the influence of various soil compaction techniques on the stability of buildings in earthquake-prone areas. It seeks to identify the most effective methods that can improve soil properties and overall structural integrity. A comparative analysis was conducted using laboratory experiments and field tests. Different compaction methods, including static, dynamic, and vibratory compaction, were applied to soil samples. The study measured parameters such as soil density, moisture content, and shear strength to assess the effects of each method on soil stability. The findings reveal that dynamic compaction significantly improves soil density and shear strength compared to static and vibratory methods. Structures built on dynamically compacted soil exhibited greater resilience to seismic forces, demonstrating lower risks of liquefaction and settlement during earthquakes. The research concludes that the choice of soil compaction method is vital for ensuring the stability of buildings in earthquake-prone regions. Dynamic compaction emerges as the most effective technique, providing enhanced soil properties that contribute to structural resilience. Future studies should explore the long-term effects of compaction methods and their implications for building codes and practices in seismic areas.